Fractured families : life on the margins in Colonial New South Wales - Evans, Tanya (UNSW Press, 2015)
Most convicts arriving in New South Wales didn't expect to make their fortunes. Some went on to great success, but countless convicts and free migrants struggled with limited prospects, discrimination and misfortune. Many desperate people turned to The Benevolent Society, Australia's first charity founded in 1813, for assistance and sustenance. In this rich and revealing book, Tanya Evans collaborates with family historians to present the everyday lives of these people. We see many families who have fallen on hard times because of drink, unwanted pregnancy, violence, unemployment or plain bad l.